SYNTHESISAND ANALYSIS OF THE HARDWARE PART’S SCHEME OF THE CYBERPHYSICAL SYSTEM “SMART ELEVATOR” - HOVORUSHCHENKO, TETIANA; VOICHUR, YURII; BARANOV, IVAN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A “smart elevator” is a modern version of a lifting device that uses microcontrollers, sensors, communication interfaces, and software to improve safety, efficiency, and ease of use. The development of the hardware part of such a system is a pressing task in the context of the digitalization and automation of domestic and industrial processes. A detailed design of the hardware part of the cyber-physical system “Smart Elevator” was carried out. During this stage, the basic requirements for the system’s component base were determined, taking into account the specifics of its functioning and the need to ensure safety and reliability of operation. Particular attention was paid to a detailed description of the system’s structural diagram, within which the functions, interrelationships, and principles of interaction of all the main hardware modules were clearly defined. The synthesis and modeling of the developed hardware diagram of the cyber-physical system “Smart Elevator” was also carried out. The design was carried out gradually, with sequential modeling and verification of the performance of each individual functional block of the system. Using Proteus’ capabilities for direct logic signal delivery, the correctness of the component selection and the correctness of their connection were confirmed. During the design, the connection features of each component and the methods of ensuring the stability of the blocks were described in detail. After modeling individual blocks, the diagram was analyzed. At this stage, a number of key functions that ensure safe and comfortable elevator operation were tested. The analysis allowed us to fully confirm the operability of the developed circuit, its compliance with the established requirements, and a high level of operational safety. This provided the necessary basis for the further implementation of the physical prototype of the system.